Transmitting and scattering colors of porous particles of poly(vinyl chloride) based on Christiansen effect. (4th July 2018) - Samitsu, Sadaki; Miyazaki, Hideki T.; Segawa, Hiroyo
Abstract: Porous poly (vinyl chloride) (PVC) particles immersed in organic liquids exhibited bright colors when the refractive indices (RIs) of the liquids were close to the RI of PVC. The particles can separate white light into complementary transmitting and scattering colors. Unlike conventional structural colors resulting from interference of light, the colors, which are independent of the periodic microstructures, were systematically tuned by varying the wavelength-dependent RIs of liquids and covered the entire visible range from 320 to 780 nm. Numerical calculation based on the Mie scattering theory successfully reproduced their transmission spectra, validating the Christiansen effect of these materials. The RI determined by this effect was higher than that of the film sample and representative values in literature. The study reveals new and undiscovered RI-related features of polymers and demonstrates that the Christiansen effect will provide a simple but valuable method to study the dispersion state of polymer particles in liquids. Graphical abstract: Image 1 Highlights: Polymer particles exhibit bright coloration without ordered arrangements. Poly (vinyl chloride) particles are suspended in refractive-index-matched liquids. Intersecting refractive index dispersion curves account for Christiansen effect. Complementary transmitting and scattering colors cover the entire visible range. Numerical calculation based on Mie scattering reproduces the experimental spectra.